Adolescents’ agency toward climate change: development and validation of scales for individual, proxy, and collective modes - Cunha, Jennifer; Martins, Juliana; Núñez, José Carlos; Vallejo, Guillermo; Rosário, Pedro (Frontiers in Psychology, 2025)
In a rapidly evolving world, human agency serves as a driving force to shape a more sustainable future. The climate crisis is an example of how individuals must be proactive and take action to mitigate this environmental problem through three modes of agency advocated by Bandura: individual, proxy, and collective. This is even more relevant for adolescents, who will most suffer climate change consequences. However, instruments assessing adolescents’ agency modes toward climate change are still lacking. To address this gap, we present the development and validation of three theoretically based scales for assessing each mode of adolescents’ agency toward climate change (AGENTC2). The AGENTC2-Scales were developed based on a literature search, expert review, and consultation with a panel of adolescents. The AGENTC2-Scales were then empirically tested with 1,114 adolescents, and their psychometric properties were assessed, providing evidence of validity (i.e., content, structural, and convergent), measurement invariance (sex and school grade), internal consistency, and test–retest reliability. Data showed that the AGENTC2-Scales can be used to measure each mode of agency toward climate change and their properties validly and reliably. Further research is needed to extend the validation of the scales in other countries.